Multidrug Efflux Systems in Microaerobic and Anaerobic Bacteria - Zeling Xu; Aixin Yan (Antibiotics, 2015)
Active drug efflux constitutes an important mechanism of antibiotic and multidrug resistance in bacteria. Understanding the distribution, expression, and physiological functions of multidrug efflux pumps, especially under physiologically and clinically relevant conditions of the pathogens, is the key to combat drug resistance. In animal hosts, most wounded, infected and inflamed tissues display low oxygen tensions. In this article, we summarize research development on multidrug efflux pumps in the medicinally relevant microaerobic and anaerobic pathogens and their implications in the effort to combat drug-resistant infections.